The Insulin Receptor: Both a Prototypical and Atypical Receptor Tyrosine Kinase - Hubbard, Stevan R. (Cold Spring Harbor Laboratory Press, 2013)
Unlike prototypical receptor tyrosine kinases (RTKs), which are single-chain polypeptides, the insulin receptor (InsR) is a preformed, covalently linked tetramer with two extracellular α subunits and two membrane-spanning, tyrosine kinase-containing β subunits. A single molecule of insulin binds asymmetrically to the ectodomain, triggering a conformational change that is transmitted to the cytoplasmic kinase domains, which facilitates their trans-phosphorylation. As in prototypical RTKs, tyrosine phosphorylation in the juxtamembrane region of InsR creates recruitment sites for downstream signaling proteins (IRS [InsR substrate] proteins, Shc) containing a phosphotyrosine-binding (PTB) domain, and tyrosine phosphorylation in the kinase activation loop stimulates InsR’s catalytic activity. For InsR, phosphorylation of the activation loop, which contains three tyrosine residues, also creates docking sites for adaptor proteins (Grb10/14, SH2B2) that possess specialized Src homology-2 (SH2) domains, which are dimeric and engage two phosphotyrosines in the activation loop.